Comparative evaluation of starch damage measurement methods and effects of heat-moisture treatment on protein structure and functional properties of pulse flours - Shen, Bei (My University, 2025)
Pulses, such as lentils, yellow pea and chickpea, are an important dietary staple worldwide, particularly in regions where plant-based proteins are central to nutrition. They are rich in proteins, vitamins, minerals, and carbohydrates such as dietary fiber and resistant starch (RS), which makes them beneficial for managing chronic diseases. This study aimed to (1) compare two methods for measuring damaged starch (DS) in pulse flours with different particle sizes, and (2) evaluate the effects of heat-moisture treatment (HMT) on protein structure and functionality in pulse flours. During dry milling to produce flours, starch granules are structurally altered, resulting in damaged starch. The level of damaged starch affects flour quality. The objectives of the first part of the study were to investigate how roller dry milling affected damaged starch content in pulse flours with different particle sizes and compare the damaged starch content measured by two methods: the amperometric (SDmatic) method (AACC 76-33.01) and the enzymatic method (AACC 76-31). For all flour types and sizes, the amperometric method consistently yielded higher damaged starch content values than the enzymatic method. For fine flours, damaged starch ranged from 3.31% (chickpea) to 4.37% (yellow pea) using the amperometric method versus 0.95–1.52% by the enzymatic method. The iodide absorption (AI%) decreased as the flour particle size increased, but higher damaged starch content was obtained from the SDmatic instrument when 1 g of flour was used. To improve the accuracy of the amperometric method when using the SDmatic instrument, a larger amount (2 g) of pulse flour was used to ensure that AI% value is greater than 86% during the amperometric measurement. After adjusting the iodide-to-damaged starch ratio, a new calibration equation was established between AI% and damaged starch content. By using the newly established equation, the amperometric method can be used to measure and obtain the damaged starch content that is correlated strongly with the enzymatic method. In addition, investigation was conducted to evaluate the effects of HMT on protein behavior in pulse flours. HMT is a physical method that can be used to modify the properties of flours without destroying starch granules. This method involves incubation of flours at low moisture content (<35% water w/w) and heating for a certain period. While much of the literature emphasizes starch behavior, fewer studies have addressed how HMT alters the protein–starch matrix. The thermal properties of pulse flours at various moisture contents (as-is, 20%, 25%, 30%, 40%, 50%, 60% and 75%) were analyzed by differential scanning calorimetry (DSC). The onset temperature was plotted against moisture content to obtain the phase diagram for the pulse flours. Pulse flours with different moisture levels of as-is, 20%, 25% and 30% were treated at 3, 6, 9, or 12 °C below the onset gelatinization temperature (based on the plotted phase diagram) for 4 hours. This part of the study systematically investigates the effects of HMT on the structural and functional properties of pulse proteins, focusing on protein solubility after pepsin treatment, hydrophobicity, and extractability. Results revealed a marked increase in non-soluble protein content after HMT, rising from 18.24% to 43.61% in yellow pea, 7.28% to 45.33% in lentil, and 12.25% to 84.94% in chickpea. Protein hydrophobicity increased for all pulse flours, reflecting structural changes induced by HMT. Additionally, HMT significantly decreased protein extractability in yellow pea and chickpea, with most treated samples falling below 70% compared to untreated controls, whereas lentil maintained high extractability (>84%) across all HMT conditions. Understanding the changes in protein during HMT would enable us to target optimization of HMT conditions to enhance the nutritional and functional performance of pulse-based ingredients in food systems.
Keywords: Pulse flours; Damaged starch; Heat-moisture treatment; Protein functionality